2014
DOI: 10.1111/jmwh.12147
|View full text |Cite
|
Sign up to set email alerts
|

Improving Maternal and Newborn Health Care Delivery in Rural Amhara and Oromiya Regions of Ethiopia Through the Maternal and Newborn Health in Ethiopia Partnership

Abstract: Introduction:In Ethiopia, rural residence and limited access to skilled providers and health services pose challenges for maternal and newborn survival. The Maternal Health in Ethiopia Partnership (MaNHEP) developed a community-based model of maternal and newborn health focusing on birth and the early postnatal period and positioned it for scale-up. MaNHEP's 3-pronged intervention included community-and facility-based community maternal and newborn health training, continuous quality improvement, and behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
126
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(131 citation statements)
references
References 15 publications
3
126
2
Order By: Relevance
“…41,52,55,67 Furthermore, 4 (80%) of the 5 studies showing no falloff or mixed results featured refresher training or regular meetings to reinforce material learned. 43,52,55,67 Two of the studies with refresher courses showed an actual increase in knowledge and skills at 1 year and 18 months after training, respectively, compared with immediately after training. 52 Of note, the 2 educational interventions from Ethiopia provided refresher training, but they also sought to educate women in the community and increase their demand for skilled maternal and newborn care, which may have been an important incentive for birth attendants to maintain their knowledge and skills.…”
Section: Retention Of Knowledge and Skillsmentioning
confidence: 99%
See 3 more Smart Citations
“…41,52,55,67 Furthermore, 4 (80%) of the 5 studies showing no falloff or mixed results featured refresher training or regular meetings to reinforce material learned. 43,52,55,67 Two of the studies with refresher courses showed an actual increase in knowledge and skills at 1 year and 18 months after training, respectively, compared with immediately after training. 52 Of note, the 2 educational interventions from Ethiopia provided refresher training, but they also sought to educate women in the community and increase their demand for skilled maternal and newborn care, which may have been an important incentive for birth attendants to maintain their knowledge and skills.…”
Section: Retention Of Knowledge and Skillsmentioning
confidence: 99%
“…37,38,48,56,66 Three studies (30.0%) showed no falloff 41,43,52 ; the 2 remaining studies (20.0%), both from Ethiopia, found varying levels of retention in different groups of birth attendants, with higher levels of training associated with less falloff. 55,67 These latter 5 studies showing either no falloff or mixed results included the 4 longest running studies in our literature review, ranging from 9 months to 2 years. 41,52,55,67 Furthermore, 4 (80%) of the 5 studies showing no falloff or mixed results featured refresher training or regular meetings to reinforce material learned.…”
Section: Retention Of Knowledge and Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The team created a network structure of one volunteer per five households 7 and collected health-related information from these households. For EBS, the community health extension workers (HEWs) instructed HDAs to report any communicable disease outbreaks and unusual health events to health posts (HPs) and HCs, particularly events with multiple deaths from unknown causes.…”
Section: Community and Health Post Levelsmentioning
confidence: 99%